Comparison of mitral regurgitant volume assessment between proximal flow convergence and volumetric methods in patients with significant primary mitral regurgitation. (4th February 2022) - Altes, A; Levy, F; Iacuzio, L; Dumortier, H; Toledano, M; Tartar, J; Tribouilloy, C; Marechaux, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Discrepancies have been observed between transthoracic echocardiography (TTE) and cardiac magnetic resonance imaging (MRI) severity grading in primary mitral regurgitation (MR). Purpose. To compare mitral regurgitant volume (RV) obtained by the proximal flow convergence method (PISA) method by TTE and by volumetric methods (TTE and MRI), and study the relationship between LV size and RV obtained by either the PISA or volumetric methods. Methods and results. 188 patients from 2 heart valve clinics with at least moderate-to-severe primary MR due to prolapse in sinus rhythm who underwent evaluation with TTE and MRI were included. RV was estimated by either PISA or volumetric methods (Left ventricular [LV] stroke volume minus systolic aortic outflow volume)) by either MRI (MRI-RV) or TTE (TTE-RV)). PISA-RV and either MRI-RV or TTE-RV weakly correlated (r = 0.29 and 0.30, p < 0.001). On multivariable analysis, LV end-diastolic volume (LVEDV) and bileaflet prolapse independently correlated with the magnitude of the difference between PISA and volumetric methods. While PISA-RV and LVEDV were unrelated, MRI-RV and TTE-RV strongly correlated with LVEDV (r = 0.66 and 0.68, p < 0.001). In contrast, LVEDV and regurgitant fraction (RF = RV/LVEDV) either with TTE or MRI were poorly related (r = 0.17, p = 0.02 and r = 0.12, p = 0.10). Conclusion. RV estimated by the PISA and volumetric methods are not comparable. The expected proportional relationship between volumetric RV and LV size, which is not observed with PISA-RV suggests the inaccuracy of PISA-RV. Given that RV by volumetric methods depends on LV size, determination of a unique RV threshold for severe MR is challenging. Calculation of RF may overcome this limitation.